2005
DOI: 10.1109/tasc.2005.849088
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cyclic Loading and Conductor Layout on Contact Resistance of Full-Size ITER PFCI Conductors

Abstract: As a final goal, the test outcome will be used as a reference for calibration of the PFCI AC loss performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
40
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 8 publications
6
40
0
Order By: Relevance
“…These confirmed that the asymptotic value of the coupling loss constant is of the order of 50 ms, in the range of the value expected from measurements on short samples [13] and well within the range acceptable from the point of view of heat removal.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…These confirmed that the asymptotic value of the coupling loss constant is of the order of 50 ms, in the range of the value expected from measurements on short samples [13] and well within the range acceptable from the point of view of heat removal.…”
Section: Discussionsupporting
confidence: 84%
“…The coupling loss measured in a short piece of the final conductors (400 mm) was found to be a strong function of the number of mechanical loading cycles under a transverse force of 315 kN/m [13], which is in the range of the maximum expected mechanical load from Lorentz forces in the ITER PF coils (270 to 330 kN/m). The initial product of demagnetization factor and coupling time constant , around 15 ms in virgin state, decreased to less than 10 ms in the first 100 cycles, to increase again above 40 ms after 10,000 cycles.…”
Section: The Pf Conductor Insertmentioning
confidence: 95%
See 1 more Smart Citation
“…In principle, the solution of the concerned 'normal equation' depends on the choice of an annular position of the petals inside the conduit. Since this position is unknown (and correlation between locations is poor due to variation in the cable twist pitch with length [12]), the solution in all three locations has been found for any combination of the rotation angles between 0 and 60 (the limits are due to periodicity of the solution) in both conductors. Then for each angle we have found an overloaded petal with the maximum deviation from the average current per petal.…”
Section: A Six-petals Problem Low Currentmentioning
confidence: 99%
“…6, the temperature increase causes a change in the self-field profile in all three locations along both conductors. Most likely the current redistribution happens through the joints as having lower contact resistances compared to inter-petal contact resistances [12] and hardly along the length, in particular for the sample with petal wraps. It is also confirmed by the resistance rise over the termination in the (see Fig.…”
Section: A Six-petals Problem Low Currentmentioning
confidence: 99%